EFFECT OF WEB BASED INSTRUCTION ON ACHIEVEMENT IN BIOLOGY IN RELATION TO INTELLIGENCE - Kaur, Mandeep; Kaur, Ravinder (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
This study analyzes the effect of web based instruction on achievement in Biology in relation to intelligence. The study investigated 320 Class IX students from Amritsar city. Achievement test in Biology of 60 items and General Group Test of Intelligence by Ahuja were used to collect the data. Experimental group was taught with the help of website named Webzbio.com and control group was taught by conventional mode of instruction. The results revealed that students achieved higher when taught through web based instruction as compared to conventional mode of instruction. Intelligence of students effected their achievement and interaction effect of instructional strategies and intelligence was found to be significant.